Perancangan Website SAKA Bhayangkara POLRES Boyolali Sebagai Sarana Informasi Dan Pendaftaran - Bayu Anggoro Tirta Kencana; Andik Prakasa Hadi; Agustinus Budi Santoso; Edwin Zusrony; Indra Ava Dianta (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to design and test the effectiveness of the Saka Bhayangkara POLRES Boyolali website as a means of information and registration. Testing was conducted on 40 users using multiple linear regression analysis with SmartPLS 4.1.1.2. The results of the study indicate that the website was successfully designed and able to assist administrative officers in the registration system to be more effective and efficient. Black-box testing confirmed that the system functioned as expected without any errors. Quantitatively, the variables Information Quality (IQ) and Service Interaction Quality (SIQ) have a significant effect on user satisfaction, while Quality of Use (UQ) has no partial effect. Thus, this website is considered effective and efficient in supporting the registration and administration process. Further research is recommended to develop a mobile-based platform such as Android.